Forms of labour in information systems - Julian Warner (Information Research: An International Electronic Journal)
A presentation open to further development is given. The idea of technology, including information technology, as a human construction is taken as the basis for the themes to be developed. The possibility of constructing an information dynamic, continuous with the dynamic of capitalism, is considered. Differentiations are made between forms of semiotic labour: semantic from syntactic labour and communal from universal labour. Information retrieval systems and the departure from the labour theory of copyright are considered in relation to the forms of labour distinguished. An information dynamic is constructed. The potential and limitations of syntactic labour are considered. The analytic value of the distinctions developed is differentiated from the possible predictive power of the dynamic indicated. The Semantic Web is viewed from the perspective of these considerations.